Non Penal Policy As A Legal Protection Effort Against Child Victims Of Sexsual Violence - Syaiful Asmi Hasibuan; Arifuddin Muda Harahap (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Sexsual violence in general often considered a crime against morality alone. The connection between sexual violence and moral issues keeps the victim silent and sometimes the victim is blamed for the violence that has befallen her. Furthermore, what happened to the victim was considered a disgrace, not only for himself but also for his family and even for the environment in which he lived. In addition, several reports indicate that the impact of sexual violence on victims is very serious, in the form of trauma that can last a lifetime for the victim, and in some cases sexual violence can incite the victim to commit suicide. Victims of sexual violence demonstrate that sexual violence can destroy the victim's entire life, leaving the victim feeling unable to continue living. So it must be recognized that sexual violence can actually threaten the sustainability of a nation and the quality of future generations. Based on the background and rationale above, it is interesting for the author to examine how non-penal policies are an effort to protect children from sexual violence in the household. The type of research used is normative legal research which is carried out by examining library data using secondary data sources, both in the form of primary legal materials and secondary legal materials as well as tertiary legal materials. This research is prescriptive in nature and uses qualitative analysis methods in explaining the relationship between the various types of data obtained so that several things can be drawn that can be concluded in this study. The use of non-penal measures, viewed from the point of view of criminal policy, occupies a key and strategic position from all efforts in overcoming criminal acts (crimes) or criminal acts, especially in the scope of sexual violence, which must be identified and made effective. Non-penal efforts are more of a preventive action, therefore the main target is to overcome the conducive factors that cause criminal acts (crimes). These conducive factors, among others, are centered on problems or social conditions that can directly or indirectly lead to or foster criminal acts. So that non-penal efforts can include activities such as providing compensation, strengthening social education in order to develop responsibility, strengthening mental health through moral and religious education. This includes activities in the context of improving community welfare efforts, monitoring and monitoring activities on an ongoing basis.